Natural Disasters and Demand for Redistribution: Lessons from an Earthquake - Giovanni Gualtieri; Marcella Nicolini; Fabio Sabatini; Luca Zamparelli (Fondazione Eni Enrico Mattei (FEEM), 2018)
The literature shows that when a society believes that wealth is determined by random “luck” rather than by merit, it demands more redistribution. Adverse shocks, like earthquakes, strengthen the belief that random “bad luck” can frustrate the outcomes achieved with merit. We theoretically illustrate that individuals react to such shocks by raising support for redistribution. We then present evidence of this behavior by exploiting a natural experiment provided by one of the strongest seismic events that occurred in Italy in the last three decades, the L'Aquila earthquake in 2009. We assemble a novel dataset by matching information on the ground acceleration registered throughout the National Strong Motion Network during the earthquake with survey data about individual opinions on redistribution collected a few months later. The empirical analysis illustrates that the intensity of the shakes is associated with subsequent stronger beliefs that, for a society to be fair, income inequalities should be levelled by redistribution.
Keywords: H10; H53; D63; D69; Z1; 330; Fairness; Redistribution; Inequality; Natural Disasters; Earthquakes